Comparison Between Refusal Rates for Organ and Cornea Donation. (August 2017) - Rennesson, C.; Moretti, D.; Arnaud, E.; Brousoz, S.; Flatres, S.; Freitas, C.; Hechinger, S.; Simon, J.; Gasche, Y.
Abstract : Introduction: When considering organ and tissue donation one needs to think about refusal rates and their reasons. In Switzerland, 80% of the Swiss population agrees with donation but the actual refusal rate is measured at 56%. In 2013, a cornea donation programme was introduced into the Geneva University Hospitals; Specialised Nurses for Organ Donation (SNOD) detect potential donors. When one is eligible, the SNOD contacts the family by telephone in order to determine the will of the deceased on donation. Our aim is to analyse the reasons for refusal. Methods: A retrospective review of 298 telephone requests was carried out between April 2013 to December 2016 and 96 files were excluded because of a lack of information. Results: Taking into consideration 202 files, the mean refusal rate was 47%. Amongst these, 37% patients had clearly expressed their refusal by informing their family with a written document such as a donor card and/or advance directives. In the remaining 63%, because the wishes were unknown, it was difficult for the relatives to make a decision; 12% mentioned the emotional incapacity to decide in the name the patient. During the same period the organ donation refusal during direct interview was 46%, quite similar to cornea donation. Of those who agreed to organ donation (54%), there was variation in the numbers of refusals for cornea donation; in donation after brain death the refusal rate was 32% versus 22% for donation after cardiac death. Because of the public reticence for ocular interventions and the difficulties of a phone call for seeking consent, we would have expected a more important difference. One of the reasons for these quite similar results is the different timing; requesting cornea donation to the relatives arises many hours after death has occurred (6-8h), acceptation of death has probably already begun and in many cases, death was expected because of a long illness. This gap in time seems to increases the consent rate for cornea donation. Conclusion: To increase the acceptation rate for organ & tissue donation, relatives should be informed of the patient's will before he dies. Our observations indicate the necessity in Switzerland to develop information campaigns concerning organ and tissue donation in general and in particular for corneas, to enable people make their own decision. Moreover, all people should be encouraged to transmit their wishes to relatives, avoiding the weight of this decision at such a sad moment.